Family Records - Brenda C. Williams; Brittany Seamon; Martie Gillen (EDIS)
This publication should be kept in a safe place known to adult members of your family and/or trusted friend(s). An additional copy should be kept in a safe deposit box. Revise it annually or after any life-changing circumstance to keep vital information current. This can make looking for vital records much faster and easier. It can also be used as a starting place for estate planning. These checklists provide suggestions on where to keep your important papers and what information to keep. This 14-page fact sheet was written by Brenda C. Williams, Brittany Seamon, and Martie Gillen, and published by the UF Department of Family Youth and Community Sciences, April 2013.